Is There a Role for Bronchial Thermoplasty in the Treatment of Asthma? - Louis-Philippe Boulet; Michel Laviolette (Canadian Respiratory Journal)
Bronchial thermoplasty is a new technique proposed to improve control of moderate to severe asthma. It delivers thermal energy to the large airways during a bronchoscopy to decrease the amount of bronchial smooth muscle. This intervention has been shown to reduce asthma exacerbations, and improve asthma control and quality of life over a three-year period without significant complications up to a five-year period. It could be considered as another option in the treatment of selected patients requiring oral and/or high doses of inhaled corticosteroids to control asthma. It should, however, be performed in specialized centres in patients who understand the potential benefits and side-effects of this technique. The response to this treatment varies from one patient to another. Consequently, further studies are required to better define the role of this option in the treatment of asthma.